Workplace stress experienced by contractor in Malaysian construction industry - Omar, Roshartini; Sallehudin, Aina Mardia (INDIAN JOURNAL OF PUBLIC HEALTH RESEARCH & DEVELOPMENT, AN INTERNATIONAL JOURNAL, 2018)
Work pressure can be experienced by any of the parties and organizations within various sectors. The work pressure issue also can be found in the construction industry, as the orientation and the nature of the job lead toward work pressure, such as organization factors, work demand factors, job roles and challenging work environment. Besides, previous studies have proven that uncontrollable of work pressure also led positively towards accident on a construction site. However, this issue had a lack of support and consensus among the parties itself. Therefore, this study is being carried out to explore the issue work stress in the Malaysian construction industry. The aim of this study is to identify the major contributor and measure work stress level in the Malaysian construction industry. The study was conducted within 78 individuals that involved from G7 class of contractors in Malacca with 74% rate of respond. This research is statistically descriptive orientation and questionnaire is being used as a research instrument. Data were analyzed by using the Statistical Package for the Social Sciences 20.0 software. Based on the results, it showed that work demand is the main factors contributing to the high-pressure jobs. Level of work stress experienced by the respondents is high, but they still have a good job in terms of achievements and satisfaction. Therefore, based on the results, all parties; DOSH, CIDB, contractors and others should take this issue seriously. The parties also need to put effort to handle the issue as its consider as an alternative to reduce the number of accidents in construction sites as well as improving performance of the industry.